2016
DOI: 10.1007/978-3-319-39763-4_12
|View full text |Cite
|
Sign up to set email alerts
|

Lessons from the South-North Migration of EU Citizens in Times of Crisis

Abstract: In this volume, we have demonstrated that-since its inception in 2008-the global financial and economic crisis has strongly impacted migration flows to/from/within the European Union as well as the way policy-makers and the public have reacted to them. While we have noted an intensification of South-North migration flows in all the case studies, the political reaction of Northern European receiving countries to this increased mobility has often seemed unrelated to the actual size of the phenomenon. Similarly, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 2 publications
0
43
0
3
Order By: Relevance
“…The testing ground of this claim and its de facto limits have been seen in recent debates among critical social policy and legal scholars, on the problematic recognition and implementation of welfare rights for EU citizens across borders. As freedom of movement has expanded quantitatively – with the accession of East and Central European member states from 2004 (Favell, ), and then new youth and labour migrations after the economic crisis in the South (Barbulescu, ; Lafleur and Stanek, ) – legal and political framings of these migrations have indeed changed. Scholarship is of course adamant that there is little evidence to substantiate one of the clear symptoms of this shift: the accusations rife in populist media and, increasingly, among mainstream politicians, about abusive “welfare tourism” and “poverty migration” by mobile EU citizens (Dustmann et al, ; Giulietti et al, ; Ehata and Seeleib‐Kaiser, ; Vargas‐Silva, ).…”
Section: European Citizenship and Welfare Rightsmentioning
confidence: 99%
See 1 more Smart Citation
“…The testing ground of this claim and its de facto limits have been seen in recent debates among critical social policy and legal scholars, on the problematic recognition and implementation of welfare rights for EU citizens across borders. As freedom of movement has expanded quantitatively – with the accession of East and Central European member states from 2004 (Favell, ), and then new youth and labour migrations after the economic crisis in the South (Barbulescu, ; Lafleur and Stanek, ) – legal and political framings of these migrations have indeed changed. Scholarship is of course adamant that there is little evidence to substantiate one of the clear symptoms of this shift: the accusations rife in populist media and, increasingly, among mainstream politicians, about abusive “welfare tourism” and “poverty migration” by mobile EU citizens (Dustmann et al, ; Giulietti et al, ; Ehata and Seeleib‐Kaiser, ; Vargas‐Silva, ).…”
Section: European Citizenship and Welfare Rightsmentioning
confidence: 99%
“…Only a few years earlier the same tabloids had raised the alarm about the arrival of Southern Europeans, young Italians, Greeks, Portuguese and Spaniards escaping the severe economic crisis at home. While absolute numbers were not spectacular, the news about the revival of the South‐North migratory routes once used by guest‐workers, had elements of triggering a new moral panic about "immigrants" (Lafleur and Stanek, ). The 2014 elections for the European Parliament brought surprises and electoral rewards for far‐right populist parties across Europe.…”
Section: Germany: Welfare Retrenchment In the Absence Of Economic Crisismentioning
confidence: 99%
“…Intra‐EU migration came under further critical scrutiny with the global financial crisis, which affected Europe as whole but most acutely impacted the weaker economies of the EU periphery, especially the southern tier of Greece, Spain, Portugal and Italy. This laid the foundations for a new wave of South‐to‐North migrations within Europe, reprising the direction of movement of the much earlier labour migrations of the early years of the Common Market from the late 1950s to the early 1970s, but this time made up disproportionately of young unemployed or career‐blocked graduates (see Lafleur and Stanek, ; also Pratsinakis et al, this issue).…”
Section: Mobilities and Crisesmentioning
confidence: 99%
“…It is often reported that EU migrants refrain from using their right to social protection in their chosen destination country either due to lack of knowledge or for fear of losing their right to residence (Lafleur and Stanek, ). This is often due to migrants’ unfamiliarity with the welfare system and the systemic differences between the sending and receiving countries (‘different types of welfare habitus’).…”
Section: A Bottom‐up Approach For Capturing Transnational Welfare Arrmentioning
confidence: 99%